2022
DOI: 10.1038/s41598-022-05790-y
|View full text |Cite
|
Sign up to set email alerts
|

Mid-wall striae fibrosis predicts heart failure admission, composite heart failure events, and life-threatening arrhythmias in dilated cardiomyopathy

Abstract: Heart failure (HF) admission is a dominant contributor to morbidity and healthcare costs in dilated cardiomyopathy (DCM). Mid-wall striae (MWS) fibrosis by late gadolinium enhancement (LGE) imaging has been associated with elevated arrhythmia risk. However, its capacity to predict HF-specific outcomes is poorly defined. We investigated its role to predict HF admission and relevant secondary outcomes in a large cohort of DCM patients. 719 patients referred for LGE MRI assessment of DCM were enrolled and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…This might be related to a more prevalent LGE distribution at middle wall of septal in DCM. Additionally, a recently published research with large sample size of DCM found that older DCM patients are more likely to show an mid wall LGE pattern, which was related to higher risk of HF readmission and adverse events [24]. Although age of DCM was similar to the whole PPCM cohort in our study, DCM patients tend to be older than acute PPCM.…”
Section: Discussionmentioning
confidence: 39%
“…This might be related to a more prevalent LGE distribution at middle wall of septal in DCM. Additionally, a recently published research with large sample size of DCM found that older DCM patients are more likely to show an mid wall LGE pattern, which was related to higher risk of HF readmission and adverse events [24]. Although age of DCM was similar to the whole PPCM cohort in our study, DCM patients tend to be older than acute PPCM.…”
Section: Discussionmentioning
confidence: 39%
“…However, up to 7% have LV dilatation without other features of idiopathic dilated cardiomyopathy [ 12 ]. Furthermore, there is a growing body of evidence that up to 8% of all MFS cases will develop secondary LV dysfunction due to significant valvular dysfunction (aortic or mitral valve regurgitation) or ischaemic heart disease, while primary LV dysfunction can be found in 3% of the MFS population [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%